The nómos, the demagogós, and the pséphisma: demagogía and democracy in Aristotle’s Politics (Argos, 2022)
This article aims to analyse the demagogoí in Aristotle’s Politics and how they are related to democracy. An examination of the portrayal of this connection has to include the importance of nómoi and psephísmata. Even though we are going to focus on books IV and V, we will take into account the whole text. It will be stated that it is possible to recognize a pejorative connotation in the lexical field even in those passages where specialists have read a neutral meaning in these words.
Keywords: Demagogoí; Politics; Aristotle; Democracy; Nómos